Interdisciplinarity , disability and inclusion: knowing to educate - Pellegrini Sara (Edukacyjna Analiza Transakcyjna)
This contribution delves into the institution of interdisciplinarity, in the light of Cognitive Motor Training, through an exploration of epistemic devices to reflect on issues relating to interdisciplinarity, disability, inclusion and the construct of Knowing to educate. The aim of the research is to reflect: